(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Increased vulnerability to antagonistic attacks, along with an increase in the number of amultipurpose structures with many functions crammed into a limited space, provides new, previouslyunexplored problem areas that are often the building code does not consider or control these items.These additional problem areas must be investigated, as well as the potential for substantial societalimplications in the event of a fire or other calamity. These issues, combined with the current lack ofguidelines for evaluation techniques, as well as well-established evaluation procedures analyticalmethods, create a necessity for a method for measuring the fire safety level in multifunctional structuresfrom a holistic perspective. Aim of this paper is to aid in Accident mitigation and repercussions in amultipurpose structure in the event of an accident or antagonistic attack.